Efficiency of using the semi-cyclic mode in a screw crystallization column - V. M. Myasoyedenkov; B. N. Shapanbayev (Тонкие химические технологии)
The theoretical analysis of the efficiency of using the semi-cyclic mode in a screw crystallization column was made. It is shown that the semi-cyclic operating mode of a column provides a higher extent of extraction of a lowmelting component than the stationary mode depending on the intensity of longitudinal mixing and on the mass exchange factor.